The COVID 19-AN OVERVIEW ON EPIDEMIOLOGY, SYMPTOMS, PREVENTION, MANAGEMENT, TREATMENT AND ROLE OF HEALTH WORKERS - BANSAL, MONISHA; WALIA, MANPREET KAUR (International Journal of Applied Pharmaceutics, 2020)
With the first case of a highly infectious virus named Coronavirus in Wuhan, China in December 2019, this deadly virus was declared a pandemic by WHO. COVID-19 was found to be very similar to patients infected with MERS-CoV and SARS-CoV. The virus was transmitted from bats to humans through some unidentified intermediary. Since its introduction in humans, it has infected 118000 people, killing 3583 till last week of May 2020 in India. The reported route of transmission is inhalation or direct contact with the infected surface or patients. This symptomatic disease includes symptoms such as cough, fever, sore throat, fatigue, and in some severe patients, it may cause multiple organ failure, pneumonia, severe or acute respiratory diseases. In some cases people may be asymptomatic till 14 d of infection. The patients with mild illness are usually isolated and others are prevented with protective measures such as medical mask, hand hygiene. In the present article, the epidemiology, route of transmission, clinical symptoms, prevention, management, treatment and role and responsibility of health workers is overviewed on the basis of published research and review articles and current state of knowledge.